The Power of Feedback to Enhance Writing Skill - Sucipto Sucipto (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Writing is not a simple task, even in the first language. Obviously, writing in the second language is more complicated. Teachers should find appropriate techniques to assist students to overcome their difficulties in learning writing. Feedback is one alternative that can be implemented in the classrooms. Teachers provide feedback to support students’ writing development and encourage their confidence as writers. Feedback plays a significant role in writing development. According to Ur (1996 : 242) feedback is information that is given to the learner about his or her performance of the learning task, usually with the objective of improving their performance. This article describes three research findings based on the classroom action research of feedback implementation in writing class. The research findings discussed in this article show that the feedback is able to help students to enhance their writing performance.